Mechanical Response of Aluminosilicate Nanotubes under Compression - González, Rafael I. (2016)
The mechanical response of aluminosilicate nanotubes (imogolite) under compression is investigated by means of classical molecular dynamics simulations using the CLAYFF potential. Using the uncompressed length L0, when there is no strain, to describe each nanotube, we have found that imogolite tends to coil for L0 > 15 nm to prevent the failure of the nanotube. The simulation also shows that the nanotubes do not break under stress for L0 ≥ 100 nm. Hence, the imogolite is a very flexible nanotube, which has been observed with lengths up to 500 nm. Finally, we can report a Young modulus of the order of 200 GPa, which is relatively independent of L0.